The Role of Celebrity Worship in the Eudaimonic Well-Being of ARMY Fandom/Fanbase Members in Indonesia - Azzahra Salsabilla Brotokusumo; Idei Khurnia Swasti (Faculty of Psychology, Universitas Semarang, 2024)
Abstract. Celebrity worship is a parasocial relationship with one or more celebrities driven by identity absorption and addiction to everything related to the celebrity. However, previous studies state that celebrity worship positively impacts the worshipers if they join the fandom. In a quantitative study design, the current study aims to determine the role of celebrity worship on the eudaimonic well-being of members of the BTS-ARMY fandom in Indonesia. There were 207 participants aged 18-25 who had joined the BTS-ARMY fandom for at least one year before the study. Data was gained using online questionnaires. The result of simple linear regression shows that celebrity worship has a positive role in eudaimonic well-being (R2=0.020; p < 0.05). By linking these two variables of the BTS-ARMY members in Indonesia, the finding contributes to understanding eudaimonic well-being in celebrity worshiping as a nonpathological activity. Further research investigation is required to support this result, for example, by focusing on the group dynamics of the fandom community.Keywords: BTS; Celebrity Worship; Eudaimonic Well-being; fandom ARMY